Functional Training Level of Runners Student-athletes Sprinters - Ikrorjon Rozikovich, Soliyev; Lilya Vladimirovna, Latibova; Bekzod Shukuralievich, Khaydrov; Isroil Ilkhomovich, Mirzatillayev; Gafur Sultonovich, Khujamkeldiyev; Farrukh Choriyorovich, Ziyayev (International Journal of Psychosocial Rehabilitation, 2020)
This article describes the results of research on the functional readiness of short-distance student athletes. The article also focuses on the optimal planning of workloads based on the formation of functional levels of student-athletes using tests of functional indicators.